Alexandria hub of the Hellenistic World - International Conference Alexandria: Hub of the Hellenistic World 2017 Bern; Schließer, Benjamin 1977-; Rüggemeier, Jan 1981-; Kraus, Thomas J. 1965-; Frey, Jörg 1962-; Herrmann, Daniel 1981-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2021)
Cover -- Titel -- Table of Contents -- Preface -- Jan Rüggemeier - Alexandria: Hub of the Hellenistic World. Introduction -- 1. Alexandria as a Multidimensional Hub -- 2. Urban Encounters and the Fragility of Alexandria's Multiculturalism -- 3. The Outline and Rationale of this Volume -- I. The City -- Gregory E. Sterling - "The Largest and Most Important" Part of Egypt: Alexandria according to Strabo -- 1. Strabo's Descriptions of Cities -- 2. Strabo's Description of Alexandria -- 3. Significant Omissions -- 4. Conclusions -- Appendix: Strabo 17.1.6-10 -- Balbina Bäbler - Whose "Glory of Alexandria"? Monuments, Identities, and the Eye of the Beholder -- 1. Introduction -- 2. Written Sources and Material Remains -- 3. Mouseion and Library: Fortress of Greekness or Multicultural University? -- 4. Places of Paideia in Alexandria: How Jews Became from Shareholders to Objects -- 5. Conclusion -- Barbara Schmitz - Alexandria: What Does the So-Called Letter of Aristeas Tell Us about Alexandria? -- 1. "The First City of the Civilized World" (Diodorus 17.52.5) -- 2. "Alexandria" in the Letter of Aristeas -- 3. Comparing Alexandria with Jerusalem and Judea in the Letter of Aristeas -- 4. Alexandria and Jerusalem -- Christina Harker - Religious Violence and the Library of Alexandria -- 1. "The Muses' Bird-Cage" -- 2. "They Are Pernicious and Ought to Be Destroyed" -- 3. "They Reckoned Their Sacrilege and Impiety a Thing to Glory in" -- 4. "A Shameful Memory, Let It Burn" -- 5. Conclusion -- Maria Sokolskaya - Was Demetrius of Phalerum the Founder of the Alexandrian Library? -- 1. The Sources and Their Value -- 2. The Ptolemeans, Alexandria, and Athens -- 3. The Role of Jewish Studies -- 4. Why Demetrius? -- II. Egyptian and Hellenistic Identities.
Alexandria was one of the main hubs of the Hellenistic world and a cultural and religious "kaleidoscope." Merchants and migrants, scientists and scholars, philosophers, and religious innovators from all over the world and from all social backgrounds came to this ancient metropolis and exchanged their goods, views, and dreams. Accordingly, Alexandria became a place where Hellenistic, Egyptian, Jewish, and early Christian identities all emerged, coexisted, influenced, and rivaled each other. Inorder to meet the diversity of Alexandria's urban life and to do justice to the variety of literary and non-literary documents that bear witness to this, the volume examines the processes of identity formation from a range of different academic perspectives. Thus, the prest volume gathers together twenty-six contributions from the realm of archaeology, ancient history, classical philology, religious studies, philosophy, the Old Testament, narratology, Jewish studies, papyrology, and the New Testament. --
Description based on publisher supplied metadata and other sources
Keywords: Alexandria (Egypt)--Antiquities--Congresses; Alexandria (Egypt)--Civilization--Congresses; Alexandria (Egypt)--Religion--Congresses; Electronic books; Antiquities; Civilization; Religion; Conference papers and proceedings; Alexandria (Egypt) -- Antiquities -- Congresses; Alexandria (Egypt) -- Civilization -- Congresses; Alexandria (Egypt) -- Religion -- Congresses; Egypt - Alexandria; Alexandria (Egypt) - Antiquities - Congresses; Alexandria (Egypt) - Civilization - Congresses; Alexandria (Egypt) - Religion - Congresses; Konferenzschrift -- 2017 -- Bern; Aufsatzsammlung